Reducing Rice Straw Burning Through Governance and Innovation: Toward Sustainable and Productive Rice Farming in Rural Malang, Indonesia - Oraby, Ghada Abd Elsattar Mohammed; Putra, Fadillah; Natsir, M. Halim; Siswanto, Dian (AGRIVITA Journal of Agricultural Science, 2026)
Rice straw burning in the open field remains a dominant activity in Singosari District, Malang Regency, Indonesia. This has several negative impacts on environmental quality and organism health, yet the implementation continues due to its perceived cost-effectiveness. The results and relevance of this article are based on findings from research conducted using a mixed-method design, including surveys, in-depth interviews, and ethnographic fieldwork. The result also shows that most smallholders (58.1%) still burned rice straw, but most of them (96.8%) would adopt green technology if they received sufficient support and facilitation. The research also indicates that farmers employing alternative methods to burning receive a 10-14% boost in yields, a good sign of what sustainability can do for food production. The major barriers to the adoption of green technology were: ignorance and lack of training (67.7%), cost of equipment (16.1%), non-availability of appropriate technology (9.7%), time constraints (6.5%), and lack of policy implementation. This study suggests that rice straw could be used as animal feed, compost, and biomass energy to mitigate pollution and meet productivity demands.